Modulação da apoptose em células BeWo infectadas por cepas atípicas (Udi1CH-05 e Udi2CH-05) de Toxoplasma gondii - Maria, Janice Buiate Lopes (2013)
Toxoplasma gondii is an obligate intracellular parasite that presents different strain types and degrees of virulence. The strains are classificated like clonal or typical and exotic or atypical. This parasite presents several evasion mechanisms, which guarantees the successful replication in the host cell and, between these mechanisms, there is ability to modulate apoptosis of infected cells as well of cells in the microenvironment of infection. The present work aimed to evaluate de ability of two atypical strains of T. gondii (Udi1CH-05 and Udi2CH-05) on modulation of apoptosis in BeWo cells, the susceptibility of these cells by infection, as well as the influence of those strains on the standard of secretion of cytokines by the trophoblastic cells lineage. These parameters were evaluated from the perspective of the immediate origin of the strains derived directly from cell culture or from animals and maintained for a short period in culture (here called Calomys callosus / culture). The Udi1CH-05 culture category upregulated apoptosis from 12 hours post infection, and from 2 hours of infection by Udi2CH-05, culture category, apoptosis was uncontrolled in BeWo cells. The condition C. callosus / culture of both strains didn t control apoptosis when compared to uninfected control. BeWo cells infected with Udi2CH-05, C. callosus / culture category produce high levels of IL-12 in the early stages of infection, suggesting a typical inflammatory response. Levels of TNF-α were higher in the early stages of infection and with a gradual decrease production, coinciding with failure to induce apoptosis when cells were infected BeWo Udi2CH-05, C. callosus / culture category. The levels of IL-10 found during infection of BeWo cells by Udi1CH-05 indicate that other cytokines may be involved in the control of infection, whereas this cytokine acts in controlling the immune response induced by infection of cells by BeWo Udi2CH-05, C. callosus / culture category. The production of TGF-β detected by infection Udi1CH-05 C. callosus / culture or Udi2CH-05 of both categories, shows that this cytokine acts in the immunoregulation of infected cells, whereas infection by Udi1CH-05, culture category, suggests that other anti-inflammatory cytokines can participate in immunoregulation, since the increase the apoptosis rate coincided with the decreased production of TGF-β.